IL-34 is associated with the presence and severity of renal dysfunction and coronary artery disease in patients with heart failure - Fan, Qin (Sci Rep, 2016)
Pro-inflammatory mediators are identified in patients with heart failure (HF), some of which may be used as biomarkers with diagnostic or prognostic value. As an additional ligand of Colony Stimulating Factor-1 Receptor (CSF-1R), interleukin-34 (IL-34) has been identified as a pro-inflammatory cytokine participating in chronic heart failure (CHF). However, the potential impact of IL-34 in CHF complications remains unknown. In order to determine the clinical significance of serum IL-34 in CHF patients, especially those with kidney dysfunction and coronary artery disease (CAD) comorbid conditions, serum IL-34 was measured in 510 consecutive patients with CHF in a cross-sectional study. The present study demonstrated that higher serum IL-34 levels were associated with poorer renal function and more severe anemia in patients with CHF. After adjusting for age, gender, conventional risk factors, and other significant covariates, IL-34 positively correlated with the presence and severity of renal dysfunction (as measured by eGFR and cystatin C) on multivariable linear and logistic regression analysis. IL-34 was also demonstrated to be an independent risk factor for CAD among HF patients. In conclusion, elevated serum IL-34 levels were demonstrated to be independently associated with renal insufficiency and CAD in patients with CHF, regardless of the systolic function.